Music visualisation with deep learning - Chong, Kyrin Sethel (Nanyang Technological University, 2023)
Music visualisation has become an integral part of music performance, appreciation and study. Even before computers, people have tried to visualise different aspects of music, from Kandinsky’s abstract paintings to Oskar Fischinger’s animated videos. Music-visual association is an innate sensory response for a small percentage of the population, known as “synaesthetes”. Even for individuals without synaesthesia, music can be associated with colours consistently enough to reach a general agreement rate.